"Putting school travel on the map": Facilitators and barriers to implementing school travel planning in Canada. Issue 3 (September 2015) - Mammen, George; Stone, Michelle R.; Buliung, Ron; Faulkner, Guy
Abstract Objective The objective of this study was to identify facilitators and barriers to effective School Travel Planning (STP) implementation. Methods Interviews were conducted with 34 Canadian STP facilitators. Participants were interviewed regarding: i) perceptions of STP success; ii) facilitators and barriers to effective STP implementation; and iii) recommendations for improving STP. A thematic analysis was used to inductively code and categorize data units into themes. Results Participants were predominantly female, worked within the health sector, and had implemented STP in the province of Ontario. All facilitators perceived STP to be successful although definitions of 'success' varied. Factors facilitating effective implementation included the well-designed STP model, collaboration between multidisciplinary stakeholders, and the facilitators׳ leadership role. Conversely, the lack of stakeholder involvement from principals, parents, and students, was identified as a barrier to effective implementation. However, the primary factor that hindered implementation was the lack of time given by funding organizations to implement STP. To observe more effective and sustainable STP interventions in Canada, the facilitators acknowledged the pressing need for multi-level government funding to develop supporting infrastructure for AST, fund facilitators, and implement policies to foster greater AST. Conclusion Overall, STP was considered successful in a variety of ways including increased awareness, rates of AST, multidisciplinary collaborations, and school-specific strategies to overcome AST barriers. The study points to a variety of factors affecting implementation. However, there was some evidence to suggest that the existing STP model is likely a short-term 'band-aid' solution to increase AST given the lack of time and sustained funding to support its implementation. Findings further call for greater investment in resources and capacity to support AST interventions like STP, particularly at the Canadian provincial and municipal levels.